ApRES data from RIS freezing sites - Irena Vankova (7046714) (2021)
ApRES data from the Ronne Ice Shelf as published in Vaňková et al. Please cite the following paper if using these data: Vaňková I., K. W. Nicholls, and H. F. J. Corr. The nature of ice intermittently accreted at the base of Ronne Ice Shelf, Antarctica, from phase-sensitive radar. Submitted.